(untitled) (Педагогіка вищої та середньої школи, 2008)
In the article T.N. Plyachenko is exposed specific of professional preparation of future music masters in the conditions of the credit-module departmental teaching, a structure and maintenance of discipline is analysed „Introduction to speciality for the students of musical separation of faculty of arts of pedagogical university.